Polled Hereford and Simmental milk production - R.R. Schalles; S. Kimbrough; K.O. Zoellner; D.D. Simms (Kansas Agricultural Experiment Station Research Reports, 1989)
The weigh-suckle-weigh method was used to measure milk consumption by 265 calves from 159 Polled Hereford and Simmental cows over 3 years. Calves nursing Polled Hereford cows consumed an average of 11.2 lbs of milk per day, with a peak of 15lbs at 50 days post"¢ calving. calves nursing Simmental cows consumed an average of 16.8 lbs of milk per day, with a peak of 20 lbs at 58 days after calving. All increase of 1lb in daily milk consumption produced approximately 20 lbs increase in weaning weight.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Hereford; Simmental; Milk production